2014
DOI: 10.1111/resp.12412
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacteria in diffuse panbronchiolitis

Abstract: Our observations suggest that NTM is found more often in DPB. Defects of mucociliary clearance may predispose individuals to NTM infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…CT evidence of collapse/consolidation was significantly correlated with isolation of Prevotella species in the bronchoalveolar lavage fluid samples using 16sRNA detecting assay . NTM was also frequently isolated from the sputum of patients with diffuse panbronchiolitis, a disease associated with bronchiectasis . These studies suggest an etiological role of NTM in the pathogenesis of bronchiectasis, which might be exacerbated by co‐infection by anaerobes that cause lung parenchyma changes on CT. Further exploration is required before therapy targeting NTM, and anaerobes can be recommended in clinical practice.…”
Section: Respiratory Infections Tuberculosis and Bronchiectasismentioning
confidence: 79%
“…CT evidence of collapse/consolidation was significantly correlated with isolation of Prevotella species in the bronchoalveolar lavage fluid samples using 16sRNA detecting assay . NTM was also frequently isolated from the sputum of patients with diffuse panbronchiolitis, a disease associated with bronchiectasis . These studies suggest an etiological role of NTM in the pathogenesis of bronchiectasis, which might be exacerbated by co‐infection by anaerobes that cause lung parenchyma changes on CT. Further exploration is required before therapy targeting NTM, and anaerobes can be recommended in clinical practice.…”
Section: Respiratory Infections Tuberculosis and Bronchiectasismentioning
confidence: 79%
“…Mycobacterium spp. also easily colonize the respiratory tract of DPB patients because DPB is accompanied mucociliary dysfunction and various bacteria colonize the respiratory epithelium [4]. NTM is a well-recognized pathogen in cystic brosis patients [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous retrospective studies have shown that diffuse panbronchiolitis, lung cancer, and rheumatoid arthritis may be associated with NTM disease [4][5][6]. Population-based studies have also identi ed comorbidities such as chronic obstructive pulmonary diseases (COPD), osteoporosis, gastroesophageal re ux (GERD), cystic brosis to be associated with NTM disease [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Colonization of the lower respiratory tract by various microorganisms occurs through diverse mechanisms, including impaired immunity in patients with underlying lung disease such as cystic fibrosis bronchiectasis and non-cystic fibrosis bronchiectasis [21,22]. Previous studies also showed that NTM was isolated in a significant proportion of these patients [23][24][25][26]. Therefore, isolation of NTM from bronchial washing or BAL may indicate colonization, especially in patients with underlying lung disease.…”
Section: Discussionmentioning
confidence: 99%